Proyecto de inversión para la creación de un centro de terapia física para mujeres embarazadas en la ciudad de Loja - Alvarado Lima, Paola Alexandra (2016)
This thesis entitled "INVESTMENT PROJECT FOR THE CREATION OF A physical therapy center for pregnant women in the city of Loja" it was done in fulfillment of the overall objective, therefore, the development of specific objectives was necessary as do a market study to determine the feasibility of the project, to develop a technical study to determine the capacity, location and optimal service process that is required for the launch of the center, analyzed through a legal administrative study, the, relevant to the establishment of the company, organizational and legal structure evaluate the project through financial analysis and indicators necessary to establish the financial feasibility of it and determine findings and recommendations. Faced with the results of the various studies determined that these are favorable, the first which corresponds to the market survey, a questionnaire was applied to a representative sample of the population, in which he could be found to exist leads you want to buy the service, as the effective demand is 34,955 women, another plus of the project is that there is a considerable range in the town has been identified as the only competitor establishment Asana Yoga Company, which is responsible for Workshops offer physical therapy to pregnant women only sporadically, which is why the total supply has been considered no great impact on the effective demand for the service, the center contains five areas of which provide the main service of physical therapy and complementary areas correspond to intrauterine stimulation services, prenatal massage, postpartum counseling, nutrition and consequently the corresponding technical study was conducted reaching determine the exact location of the company will be in the city of Loja in the sector Strong Military Minacho out in the streets Eduardo Kingman, among Saraguro and Alamor, will have an installed 6 capacity to provide services 22,120 per year capacity, but as a company that capacity utilization for the first year newly emerged in the market will be 70% of installed and increasing by 10% each year up to provide 100% of the installed in the same manner so that there is a uniform distribution of each of the areas the plant design was performed and determined the due instruments and materials necessary for a technical, safe, and comfortable infrastructure that will allow users greater comfort. Subsequent to this based on the organizational study found that the establishment of the company will be a limited liability company, under the name "TAPE" with a number of four partners, mission, vision, objectives was also designed to follow values and principles, in addition to its proper management, it will be organized with the relevant hierarchical levels, both their structural, functional and positional, with different functions and manual and safety at work flowcharts; which allow you to technically develop its administrative process, to meet the different guidelines that must be met. Finally with regard to the financial study it came to determine the total amount of investment amounts to $ 27,873.57 whose value will be funded at 100% by the partners. Similarly the projected operating budget of the first five years of the project is contemplated, establishing a net return on sales of 20% for all years, so the project is considered profitable for the investor. Financial evaluation was also performed, same as after the analysis made all indicators, it is determined that the development of this project is feasible, since the time that the company will take to recoup the investment will be in 1 year 7 months 13 days, a net present value of $ 40,251.12, the cost benefit ratio of 1,20, the 7 internal rate of return of 56.22%, in the sensitivity analysis, it was determined that the project supports an increase in costs of 11.1596% and a decrease in revenue of 9.2997%. In conclusion it was determined that the Center for Physical Therapy for Pregnant Women in the city of Loja, is a feasible plan of business, for which it is recommended to start the project, as through it was determined the existence of unmet demand in the market, being an innovative project will contribute to the business growth of the city.